A Switched-Capacitor-Based 7-Level Self-Balancing High-Gain Inverter Employing a Single DC Source - Yatindra Gopal; Kaibalya Prasad Panda; Akanksha Kumari; Julio C. Rosas-Caro (International Transactions on Electrical Energy Systems)
This paper discloses a novel switched capacitor (SC)-based 7-level inverter with a single DC source. The proposed inverter has the ability to self-balancing the voltage of the capacitor without using a closed-loop voltage balancing circuit. Two capacitors are equally charged by the input source owing to the series-parallel charging and discharging continuously in a full cycle. The proposed 7-level SC inverter requires less number of switches, driver diodes, and capacitors and a lower number of semiconductor switches than most recently developed topologies. Furthermore, four out of the eight switches operate at the fundamental frequency, which simplifies the control scheme. A fundamental frequency switching scheme is used to control the output of the inverter. The self-balancing and voltage-boosting features of the proposed structure are validated on MATLAB/software platform and verified experimentally.